PENGGUNAAN METODE PROYEK UNTUK MENINGKATKAN KEDISIPLINAN PADA ANAK USIA DINI - Endin Mujahidin M.Si; Lailatul Mufarohah; Akhmad Alim (Edukasi Islami : Jurnal Pendidikan Islam, 2019)
Children’s discipline in some kindergartens is relatively low. It causes difficulties for teachers to prepare children before learning activity or class begin. Currently, most of teachers’s learning tend to be monotonous so the children are easily bored and no passion in doing assignments. Therefore an innovative learning method is needed to improve children's discipline. The objective of this study was to evaluate the project method on increasing of little children’s discipline. The study was conducted at RA Al-Hidayah, Kemang, Bogor Regency, using a number of 44 children as sample. Research method used was experimental design with pretest-posttest control group. Collecting data was performed by observation and documentation. The results of this study showed that discipline of children treated by project method was significantly higher than untreated group. It concluded that the project method can be recommended to apply in kindergarten to increase discipline. Keywords: discipline, early childhood, project method.